3D printed perforated QR codes. (June 2019) - Yang, Jingru; Peng, Hao; Liu, Lin; Lu, Lin
Highlights: A problem for carving a QR code on a surface such that the 3D printed QR code with homogeneous material is decodable. A method for automatically generating the fabricable perforated QR codes. An evaluation function to quantitatively measure the readability of the QR code. An optimization framework for optimizing the QR code into a 3D printable model, considering the QR readability. Graphical abstract: Abstract: QR codes are machine-readable optical 2D matrix barcodes which can be easily displayed physically on printed media or digitally on a screen. In recent years, artists and researchers have paid much attention to beautify and enhance QR codes with visual features beyond their plain standard format. We propose a novel method for carving a QR code on a surface in a perforated manner and fabricating it with single material via ordinary 3D printing techniques. However, it is nontrivial to directly fabricate such artistic QR codes because there are a large amount of disconnected components and small details that are difficult to be fully realized. To this end, the embedded information must be consistent and the 3D printed QR code should be readable with standard decoders, like mobile phones. With the original code, we introduce a QR evaluator to estimate its readability and then optimize the code in terms of the printability and robustness. We demonstrate the effectiveness of our techniques with a wide range of examples printed with homogeneous materials via consumer-level 3D printers.